2021
DOI: 10.1186/s12915-021-00981-x
|View full text |Cite|
|
Sign up to set email alerts
|

Insights into the demographic history of Asia from common ancestry and admixture in the genomic landscape of present-day Austroasiatic speakers

Abstract: Background The demographic history of South and Southeast Asia (S&SEA) is complex and contentious, with multiple waves of human migration. Some of the earliest footfalls were of the ancestors of modern Austroasiatic (AA) language speakers. Understanding the history of the AA language family, comprising of over 150 languages and their speakers distributed across broad geographical region in isolated small populations of various sizes, can help shed light on the peopling of S&SEA. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 67 publications
(70 reference statements)
2
13
0
Order By: Relevance
“…Nevertheless, the presence of ancient Austroasiatics (AA) speakers across NEI still remains a possibility. Our previous study (Tagore et al, 2021) on autosomal data of the Mundari and Mon-Khmer Austroasiatics indicated that in pre-Neolithic times, the ancestors of today's Austroasiatic speakers had a widespread distribution possibly extending from Central India to Southeast Asia (SEA), further supported by Lipson et al (2018). They were later in time fragmented and isolated to small pockets resulting in their present-day disjoint geographic distribution.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, the presence of ancient Austroasiatics (AA) speakers across NEI still remains a possibility. Our previous study (Tagore et al, 2021) on autosomal data of the Mundari and Mon-Khmer Austroasiatics indicated that in pre-Neolithic times, the ancestors of today's Austroasiatic speakers had a widespread distribution possibly extending from Central India to Southeast Asia (SEA), further supported by Lipson et al (2018). They were later in time fragmented and isolated to small pockets resulting in their present-day disjoint geographic distribution.…”
Section: Introductionmentioning
confidence: 95%
“…Basu et al (2003) has shown that the TB and AA speakers of India are similar in their mtDNA profile but harbor very distinct Y-chromosomes. Our previous study (Tagore et al, 2021) observed the genetic relatedness between the Tibeto Burmans and Austroasiatic speakers (Mon Khmers) of Malaysia, because of ancient shared ancestry as well as owing to gene flow in both these populations from East Asia. Another study (Guo et al, 2022) found the present day TBs to cluster between the millet cultivators of Yellow River basin as well as the Austroasiatic speakers of Southeast Asia in a Principal Components Analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigation postulates that pre-Neolithic ancestors of today’s Austroasiatic language-speaking populations were widespread in South Asia and SEA, and the populations from these regions were the result of multiple migrations of East Asian farmers during the Neolithic period ( Tagore et al, 2021 ). The authors predicted that the present-day Austroasiatic populations from India and Malaysia shared a common ancestor until about 10.5 kya.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], an error was identified in the ‘Availability of data and materials’ section due to a typesetting mistake: in the first sentence of this section, a citation to reference 76 was present, instead of a citation to reference 72.…”
mentioning
confidence: 99%
“…The original article [ 1 ] has been updated. The publisher apologises to the authors and readers for the inconvenience caused by this mistake.…”
mentioning
confidence: 99%